Analisis Bentuk Campur Kode Content Creator Pada Akun @furkysyahroni di Aplikasi TikTok (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the form of code mixing content creators on the TikTok application. Data in the form of words, phrases, and clauses, the data source of this study is code mixing content creators in the video account @furkysyahroni found in the TikTok application. The data collection method uses the reading method. Basic tapping techniques and advanced reading techniques free from conversational involvement . The results of the study found code mixing forms in the form of words, phrases, and clauses. The conclusion of the author's research found 21 data from the video of 1 content creator uploaded by @furkysyahroni on the TikTok application . Of these, 13 data are included in the category of code mixing forms of word insertion, 7 data are code mixing forms of phrase insertion, and 1 data is code mixing forms of clause insertion.